Integrating Local Wisdom in Science: Development and Validation of Ethnoscience Teaching Modules for Improving Science Literacy of Junior High School Students - Sutanto, Taufiq; Akhsan, Hamdi; Kistiono, Kistiono (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The low level of science literacy among Indonesian students requires innovative and contextual learning approaches. This study aims to develop and test the validity of an Ethnoscience-Based Teaching Module on the subject of Vibrations and Waves. The uniqueness of the module lies in its deep integration of the local wisdom of East OKU Regency as a learning context to bridge abstract scientific concepts with the cultural reality of students. Methodology: This study used the Research and Development (R&D) method with a 4-D model, limited to the Develop stage. Validation was carried out by four experts (material, media, language, and culture) using adapted assessment instruments. Quantitative data were analyzed using Aiken's V coefficient. Main Findings: The developed ethnoscience-based teaching module was declared